(untitled) (Research, Society and Development, 2021)
Originated in the last three decades of the 20th century, tightly influenced by the techno-linguistics, an enunciative language emerges with more semiosis than it was before, bringing with it a varied range of genres, permeated by social arrangements, with different compositional characteristics and communicative purposes. By the genre that the communication is stablished by the language. From a bibliographic research, this article has as the mainly purpose to clarify the similarities and distinctions among the different genre theory encompassing specially the theory of Bakhtin (1997), the sociosemiotic approach from Hasan (1995), Martin (1984) and Kress (1997) and the socio-rhetoric approach from Swales (1190), Miller (1994) and Bazerman (1994). From this research on, it was possible to stablish a parallel considering the theoretical developments of genre coined by different authors and the concepts that have been enriching the researches in the Linguistic and Applied Linguistics. This theoretical discussion is divided in two sections, being the first about the concept and the second about the theoretical developments about the genre perspectives.